Hubungan antara Jarak dan Status Gizi dengan Kejadian Pre Eklamsi pada Ibu Hamil di RS Aura Syifa Kediri: The relationship between distance and nutritional status with the incidence of pre-eclampsia in pregnant women at Aura Syifa Hospital, Kediri - Wulandari, Siswi (Universitas Muhammadiyah Sidoarjo, 2016)
Preeclampcy is poisoning in pregnancy accompanied with hypertension, proteinuria, oedema, and occurs at the age of more than 20 weeks of pregnancy or shortly after birth. The cause of the preeclampcy could be caused by the distance of the pregnancy and nutritional status. Figure preeclampcy occurrence in an area can be an indicator of the level of public health in the area. The purpose of this research is to know the existence of the relationship between the distance of the pregnancy and nutritional status with the preeclampcy in pregnant women at Aura Syifa Hospital Kediri Regency in 2015. The research design used was an analytic research corelasional by using the approach of cross sectional. The population examined was the pregnant women at RS Aura Syifa Kediri Regency in 2015 from July-August totaled 549 people with engineering probability sampling simple random sampling type retrieved samples of 85 people. The variables measured were distance of the pregnancy and nutrient status as an independent, preeclampcy as the dependent variable. The research result was analyzed by spearman rank. The results showed most of the distance of the pregnancy is on categories ideal 2-5 years (61 71,8%), nutrient status is on normal category 23, 5 cm-25 cm 70 people (82.3%), and most have no preeclampcy 54 (63,6%). There is a relationship between the distance of pregnancies and nutritional status and the incidence of preeclampcy in pregnant women at Aura Syifa Hospital Kediri Regency in 2015.